Exploring the relationship between consciousness and repurchase intention among Malaysian consumers - Teh Yen Sin; Hamid Rizal; Anath Rau Krishnan; Hanudin Amin; Chen, Jung Ku (Universiti Malaysia Sabah, 2024)
The aftermath Covid-19 pandemic has reshaped consumer purchasing behavior. Driven by the need to avoid physical contact, people have become even more accustomed to purchasing via mobile. This phenomenon has resulted in changes in consumer purchasing behavior and habits, with many customers scrutinizing brands and pricing before making online purchases. This study used the stimulus-organism-response (S-O-R) paradigm to examine consumers’ consciousness behavior to explore information quality and perceived risk toward repurchase intention in Malaysia. Online questionnaires were disseminated to 149 mobile shopping users in Malaysia using a quantitative approach. The results demonstrated that information quality and perceived risk substantially affect awareness. The respondents only indicated information quality as a significant indicator for repurchase intent, and the study offers support on consciousness as a mediator between perceived risk and repurchase intention. The study has practical implications for online merchants and mobile commerce developers that seek to understand better consumer preferences and trends.